APAKAH MEREKA BEKERJA? STUDI REALITAS OBJEKTIF AKTIVITAS MENGEMIS DI TULUNGAGUNG - Prasetyo Adi Nugroho; Nindya Nurdianasari; Hari Satrijono (Jurnal Pendidikan Ilmu Sosial, 2022)
This study aims to analyze people's perceptions regarding the act of begging as a work activity, so that the status of the existence of begging activities can be obtained. This study uses a qualitative research design. The research was conducted in Tulungagung from January 2020 to January 2021. The research subjects were 10 people who had experience interacting with beggars. Collecting data using thematic interviews as an approach. The results of the study showed that the respondents dominantly made the perception that the activity of begging was a work activity. This is indicated by the informant's findings that 1) beggars seek a certain income; 2) begging is considered the easiest alternative to earn money; 3) beggars are considered lazy to work in the formal realm. The perception of begging as a work activity is driven by the perception that beggars apply an attempt to lie by displaying a symbol of poverty to obtain maximum income. So that begging is placed in a fair status with consideration, beggars are individuals who are lazy to work and beggars are parents and people with physical disabilities. Taking into account the existence of prevailing norms, the informants placed the activity of begging as a work activity in a pathological position and had implications for the rejection of the existence of begging activities. Rejection is represented by a response negligence acts as a cultural treatment and arrests, coaching, and repatriation of perpetrators are carried out as institutional treatment.